Utility of 7 Tesla MRI for Preoperative Planning of Endoscopic Endonasal Surgery for Pituitary Adenomas - Rutland, John W.; Delman, Bradley N.; Feldman, Rebecca E.; Tsankova, Nadejda; Lin, Hung-Mo; Padormo, Francesco; Shrivastava, Raj K.; Balchandani, Priti (Journal of Neurological Surgery Part B: Skull Base, 2019)
Objective There is increasing interest in investigating the utility of 7 Tesla (7 T) magnetic resonance imaging (MRI) for imaging of skull base tumors. The present study quantifies visualization of tumor features and adjacent skull base anatomy in a homogenous cohort of pituitary adenoma patients.Methods Eighteen pituitary adenoma patients were scanned at 7 T in this prospective study. All patients had reference standard-of-care clinical imaging at either 3 T (7/18, 39%) or 1.5 T (11/18, 61%). Visualization of tumor features and conspicuity of arteries and cranial nerves (CNs) was rated by an expert neuroradiologist on 7 T and clinical field strength MRI. Overall image quality and severity of image artifacts were also characterized and compared.Results Ability to visualize tumor features did not differ between 7 T and lower field MRI. Cranial nerves III, IV, and VI were better detected at 7 T compared with clinical field strength scans. Cranial nerves III, IV, and VI were also better detected at 7 T compared with only 1.5 T, and CN III was better visualized at 7 T compared with 3 T MRI. The ophthalmic arteries and posterior communicating arteries (PCOM) were better detected at 7 T compared with clinical field strength imaging. The 7 T also provided better visualization of the ophthalmic arteries compared with 1.5 T scans.Conclusion This study demonstrates that 7 T MRI is feasible at the skull base and identifies various CNs and branches of the internal carotid artery that were better visualized at 7 T. The 7 T MRI may offer important preoperative information that can help to guide resection of pituitary adenoma and reduce operative morbidity.
Keywords: 7 Telsa MRI; pituitary adenoma; endoscopic endonasal surgery; skull base anatomy; neurosurgery